The cytotoxic activities of the major diterpene extracted from Salvia multicaulis (Bardakosh) are mediated by the regulation of heat-shock response and fatty acid metabolism pathways in human leukemia cells - Nabih, Heba K.; Yücer, Rümeysa; Mahmoud, Nuha; Dawood, Mona; Elbadawi, Mohamed; Shahhamzehei, Nasim; Atia, Mohamed A. M.; AbdelSadik, Ahmed; Hussien, Taha A.; Ibrahim, Mahmoud A. A.; Klauck, Sabine; Hegazy, Mohamed-Elamir F.; et al. (Phytomedicine, 2024)
Background - Leukemia is one of the most lethal cancers worldwide and represents the sixth-leading cause of cancer deaths. The results of leukemia treatment have not been as positive as desired, and recurrence is common. - Purpose - Thus, there is an urgent requirement for the development of new therapeutic drugs. Salvia multicaulis (Bardakosh) is a widespread species that contains multiple phytochemical components with anti-cancer activities. - Methods - We isolated and characterized the major diterpene candesalvone B methyl ester from S. multicaulis and investigated its action as a cytotoxic agent towards sensitive and drug-resistant leukemia cells by the resazurin reduction assay. Additionally, the targeted genes and the affected molecular mechanisms attributed to the potent cytotoxic activities were discovered by transcriptome-wide mRNA expression profiling. The targets predicted to be regulated by candesalvone B methyl ester in each cell line were confirmed by qRT-PCR, molecular docking, microscale thermophoresis, and western blotting. Moreover, cell cycle distribution and apoptosis were analyzed by flow cytometry. - Results - Candesalvone B methyl ester was cytotoxic with IC50 values of 20.95 ± 0.15 µM against CCRF-CEM cells and 4.13 ± 0.10 µM against multidrug-resistant CEM/ADR5000 leukemia cells. The pathway enrichment analysis disclosed that candesalvone B methyl ester could regulate the heat-shock response signaling pathway via targeting heat shock factor 1 (HSF1) in CCRF-CEM cells and ELOVL fatty acid elongase 5 (ELOVL5) controls the fatty acid metabolism pathway in CEM/ADR5000 cells. Microscale thermophoresis showed the binding of candesalvone B methyl ester with HSF1 and ELOVL5, confirming the results of molecular docking analysis. Down-regulation of both HSF1 and ELOVL5 by candesalvone B methyl ester as detected by both western blotting and RT-qPCR was related to the reversal of drug resistance in the leukemia cells. Furthermore, candesalvone B methyl ester increased the arrest in the sub-G1 phase of the cell cycle in a dose-dependent manner from 1.3 % to 32.3 % with concomitant induction of apoptosis up to 29.0 % in CCRF-CEM leukemic cells upon inhibition of HSF1. - Conclusion - Candesalvone B methyl ester isolated from S. multicaulis exerted cytotoxicity by affecting apoptosis, cell division, and modulation of expression levels of genes contributing to the heat stress signaling and fatty acid metabolism pathways that could relieve drug resistance of leukemia cells.
Online verfügbar: 27. September 2024, Artikelversion: 04. Oktober 2024
Gesehen am 24.04.2025